The Ratio of the Distal Femur Width to the Tibial Plateau Width with Advancing Age - Schlatterer, Daniel Robert; Kessler, Raymond; Donahue, Jeffrey; Amersi, Arish; Robinson, Weston; Khakharia, Saurabh (The Journal of Knee Surgery, 2021)
Historically, intraoperative analysis of knee fracture procedures relied upon a fluoroscopic reduction assessment by the surgeon. This is a subjective assessment due to the lack of linear measurement reference data. Compared with the knee, the ankle and wrist have well-established bony anatomical relationships to guide reduction assessment during fracture treatment. The purpose of this study was to (1) determine the width ratios in the knee (plateau to femur) with aging, and (2) determine knee width changes with aging. One-hundred and fifty consecutive uninjured knee radiographs were reviewed. In all age groups, the width ratio of the articular distal femoral (ADF) to the articular tibial plateau (ATP) is greater than 1.0 and between 1.03 and 1.05. The tibia plateau width is on average 9.34 mm wider and the femoral width is 8.0 mm wider in the 61 to 80 age group than the ATP and the ADF in the younger age groups. In conclusion, the articular tibial plateau width and the articular distal femoral width are nearly equal across ages 20 to 80 years. An absolute articular width value by age cannot be assigned because articular widths change with aging.
Keywords: distal femur; tibial plateau; width; ratios; advanced age